Acceptability of a behavioural intervention to mitigate the psychological impacts of COVID-19 restrictions in older people with long-term conditions: a qualitative study. Issue 3 (13th March 2023) - Shearsmith, Leanne; Coventry, Peter A; Sloan, Claire; Henry, Andrew; Newbronner, Liz; Littlewood, Elizabeth; Bailey, Della; Gascoyne, Samantha; Burke, Lauren; Ryde, Eloise; Woodhouse, Rebecca; McMillan, Dean; et al.
Abstract : Objectives: The COVID-19 pandemic heightened the need to address loneliness, social isolation and associated incidence of depression among older adults. Between June and October 2020, the Behavioural Activation in Social IsoLation (BASIL) pilot study investigated the acceptability and feasibility of a remotely delivered brief psychological intervention (behavioural cctivation) to prevent and reduce loneliness and depression in older people with long-term conditions during the COVID-19 pandemic. Design: An embedded qualitative study was conducted. Semi-structured interviews generated data that was analysed inductively using thematic analysis and then deductively using the theoretical framework of acceptability (TFA). Setting: NHS and third sector organisations in England. Participants: Sixteen older adults and nine support workers participating in the BASIL pilot study. Results: Acceptability of the intervention was high across all constructs of the TFA: Older adults and BASIL Support Workers described a positive Affective Attitude towards the intervention linked to altruism, however the activity planning aspect of the intervention was limited due to COVID-19 restrictions. A manageable Burden was involved with delivering and participating in the intervention. For Ethicality, older adults valued social contact and making changes, support workers valued being able to observe those changes. The intervention was understood by older adults and support workers, although less understanding in older adults without low mood (Intervention Coherence). Opportunity Cost was low for support workers and older adults. Behavioural Activation was perceived to be useful in the pandemic and likely to achieve its aims (Perceived Effectiveness), especially if tailored to people with both low mood and long-term conditions. Self-efficacy developed over time and with experience for both support workers and older adults. Conclusions: Overall, BASIL pilot study processes and the intervention were acceptable. Use of the TFA provided valuable insights into how the intervention was experienced and how the acceptability of study processes and the intervention could be enhanced ahead of the larger definitive trial (BASIL+).